Accelerated atherosclerosis in autoimmune rheumatic disease - Doria, Andrea (Henry Stewart Talks, 2007)
Immunoinflammatory mechanisms involved in atherosclerosis, Autoantibodies and atherosclerosis, Clinical and subclinical atherosclerosis in rheumatoid arthritis, Clinical and subclinical atherosclerosis in systemic lupus erythematosus, Traditional and non-traditional risk factors for atherosclerosis in autoimmune rheumatic diseases, Assessment of endothelial function in autoimmune rheumatic diseases, Endothelial dysfunction in autoimmune rheumatic diseases
Archived at 2018/05/31